Angiogenic CD34+CD146+ adipose‐derived stromal cells augment recovery of soft tissue after radiotherapy. (5th October 2021) - Deleon, Nestor M. Diaz; Adem, Sandeep; Lavin, Christopher V.; Abbas, Darren B.; Griffin, Michelle; King, Megan E.; Borrelli, Mimi R.; Patel, Ronak A.; Fahy, Evan J.; Lee, Daniel; Shen, Abra H.; Momeni, Arash; et al.
Abstract: Radiation therapy is effective for cancer treatment but may also result in collateral soft tissue contracture, contour deformities, and non‐healing wounds. Autologous fat transfer has been described to improve tissue architecture and function of radiation‐induced fibrosis and these effects may be augmented by enrichment with specific adipose‐derived stromal cells (ASCs) with enhanced angiogenic potential. CD34+CD146+, CD34+CD146−, or CD34+ unfractionated human ASCs were isolated by flow cytometry and used to supplement human lipoaspirate placed beneath the scalp of irradiated mice. Volume retention was followed radiographically and fat grafts as well as overlying soft tissue were harvested after eight weeks for histologic and biomechanical analyses. Radiographic evaluation revealed the highest volume retention in fat grafts supplemented with CD34+CD146+ ASCs, and these grafts were also found to have greater histologic integrity than other groups. Irradiated skin overlying CD34+CD146+ ASC‐enriched grafts was significantly more vascularized than other treatment groups, had significantly less dermal thickness and collagen deposition, and the greatest improvement in fibrillin staining and return of elasticity. Radiation therapy obliterates vascularity and contributes to scarring and loss of tissue function. ASC‐enrichment of fat grafts with CD34+CD146+ ASCs not only enhances fat graft vascularization and retention, but also significantly promotes improvement in overlying radiation‐injured soft tissue. This regenerative effect on skin is highly promising for patients with impaired wound healing and deformities following radiotherapy.